Mobilizing bodies: unsettling sustainable mobility through cycling in Los Angeles - Davidson, AC (2017)
The figure of the human body and notions of its sustenance, wellbeing and need for change are central, if often latent, within discussions of contemporary eco-social 'crises'. This dissertation considers cycling practices in Los Angeles as a 'case' to ask how conceptions of human bodies - the intertwined ideas and materials that constitute them –need reconsidering. Cycling, particularly when replacing car journeys, is increasingly promoted as a solution for some of these 'crises': Reducing greenhouse gas emissions, air pollution, traffic congestion and alleviating health concerns associated with sedentary lifestyles and mental health. Much cycling advocacy and research is focused on improving the cycling experience and enhancing rates of cycling in cities, yet rests on dominant ontological presumptions around human bodies, their categories of identity and their normativity - both what is considered 'normal' as well as aspirations of 'good' in terms of health and sustainability. In this dissertation, I work through a methodology of 'riding theory' by bringing together (material) feminist, queer and critical race theories with multi-sited ethnographic fieldwork on cycling practices, focusing mainly on Los Angeles, California. Rather than building on automatic assumptions of cycling as a 'solution', I ask in what ways cycling practices manifest through relations of power. This rests on an ontology of 'flesh' and 'enfleshment' – indebted to the work of corporeal and black feminist theorists - whereby cycling is understood not as modulated by relations of power, but becoming-as and through these relations in highly uneven ways. Through cycling in Los Angeles, intertwined techniques of power are discussed as: categorization (the naming and reproduction of identities and bodily difference); configuration of matter and meanings through spacetime (the configuration and affordances of cycling lungs, exposures, taking up spacetimes, speeds and locomotion) and valuation (the enrolment of cycling subjectivities and energies within the reproduction and circulation of value). As opposed to cycling futures reconfigured to fulfil alternative criteria of valuation, I consider what a cycling ethic of response-ability might do: An ethic that arises from the ontologies of enfleshment and that requires a working-with the affordances of cycling. Thinking through these ontologies and/as ethics, I argue, forces emergent reconsideration of how cycling subjectivities and responsibilities, justice, health and sustainability are understood.